Does Postsecondary Persistence in STEM Vary by Gender? - Barbara King (SAGE Publishing, 2016)
The underrepresentation of women in science, technology, engineering, and mathematics (STEM) is often explained by women's greater likelihood to leave STEM at each key juncture from elementary school into the workforce. It is important to examine this more closely and look for points in the pipeline where gender equity exists. This study uses nationally representative data from a recent cohort of college students to investigate thoroughly gender differences in STEM persistence. Results indicate that no significant gender differences in persistence exist. This finding holds among those in computer science, engineering, mathematics, and physical science, and for those in life science. Additionally, the results are unchanged if the sample is limited to degree earners and are robust to the inclusion of individual and institutional variables. Although it is clear that women are less likely to choose certain STEM majors, those who do are no less likely to earn a STEM degree.